Teeth movement in denture and implant-supported prosthesis influenced by microwave flask systems - Rafael L.X. Consani; Leonardo G. Sonehara; Marcelo F. Mesquita; Valentim A.R. Barão; Conrado R. Caetano (Journal of Oral Biology and Craniofacial Research)
Background/Aims: This study evaluated the teeth movement in maxillary dentures and mandibular implantsupported prostheses processed by microwave flasks. Methods: A model mounted on articulator was used to manufacture Co-Cr frameworks. Pins were placed for measurements on the incisal edge of upper and lower central incisors (I), buccal cusp of first upper and lower premolars (PM), and mesiobuccal cusps of upper and lower second molars (M). Distances I-I (incisor to incisor), PM-PM (premolar to premolar), M-M (molar to molar), RI-RM (right incisor to right molar), and LI-LM (left incisor to left molar) were measured before and after processing using a microscope (0.0005 mm). Vertical misfit between abutment and implant platform was evaluated for regions A (left distal implant), B (left median implant), C (medial implant), D (right median implant), and E (right distal implant) in predetermined labial and lingual sites. Prostheses were divided into groups G1 – conventional flask, and G2 – experimental HH flask. Acrylic resin was microwaved at 1400 W (30% for 3 min, 0% for 3 min, and 60% for 3 min). Horizontal teeth displacement and vertical misfit between abutment and implant platform were considered before and after procedures. Data were submitted to three-way ANOVA and Tukey's test (α = 0.05). Results: Except for M-M distance, the teeth showed displacements without statistical difference for prosthesis and flask factors. There was no significant difference for vertical misfit values for both flasks. Conclusion: Diferente flasks did not cause significant changes in the teeth displacement, except for M-M. Vertical misfit values were not influenced by the flasks.